Addressing Disparities Using Continuous Glucose Monitors and Remote Patient Monitoring for Youth With Type 1 Diabetes - Lee, Ming Yeh; Ritter, Victor; Shaw, Blake; Ferstad, Johannes O; Johari, Ramesh; Scheinker, David; Bishop, Franziska; Desai, Manisha; Maahs, David M; Prahalad, Priya (Journal of diabetes science and technology, 2024)
Youth with type 1 diabetes (T1D) and public insurance have lower diabetes technology use. This pilot study assessed the feasibility of a program to support continuous glucose monitor (CGM) use with remote patient monitoring (RPM) to improve glycemia for youth with established T1D and public insurance. From August 2020 to June 2023, we provided CGM with RPM support via patient portal messaging for youth with established T1D on public insurance with challenges obtaining consistent CGM supplies. We prospectively collected hemoglobin A (HbA ), standard CGM metrics, and diabetes technology use over 12 months. The cohort included 91 youths with median age at enrollment 14.7 years, duration of diabetes 4.4 years, 33% non-English speakers, and 44% Hispanic. Continuous glucose monitor data were consistently available (≥70%) in 23% of the participants. For the 64% of participants with paired HbA values at enrollment and study end, the median HbA decreased from 9.8% to 9.0% ( < .001). Insulin pump users increased from 31 to 48 and automated insulin delivery users increased from 11 to 38. We established a program to support CGM use in youth with T1D and barriers to consistent CGM supplies, offering lessons for other clinics to address disparities with team-based, algorithm-enabled, remote T1D care. This real-world pilot and feasibility study noted challenges with low levels of protocol adherence and obtaining complete data in this cohort. Future iterations of the program should explore RPM communication methods that better align with this population's preferences to increase participant engagement.